Supporting Human Memory with a Personal Digital Lifetime Store - Tan, Desney; Berry, Emma; Czerwinski, Mary; Bell, Gordon; Cemmell, Jim; Hodges, Steve; Kapur, Narinder; Meyers, Brian; Oliver, Nuria; Robertson, George; Woodberry, Ken (Personal Information Management Edited by William Jones and Jaime Teevan, 2007)
One of the things that distinguishes human beings from other species is the magnitude to which we manipulate our (largely synthetically created) environments and our technologies in order to augment ourselves physically and mentally. Supporting our individual as well as collective memory has been a particularly important endeavor as we have continued to build upon past experiences and improve our way of life. We are now at a time when each of us is generating and handling more information than ever before. Fortunately, we are now also equipped with technologies that can begin to record, store, summarize, and retrieve all this content. Various governments have recognized the potential of realizing these augmentations and created programs to fund work in the area, as for example in Memories for Life Grand Challenge in the UK, Fitzgibbon and Reiter (2003), and the LifeLog program in the United States (DARPA, n.d.), the work of which has now been distributed into multiple other programs. In chapter 3 of this book, Jones describes the distinction between information keeping, whereby a user decides what to store, and information organizing, the creation of the structures within which information is stored and retrieved. He reviews strategies and tools that make decisions about keeping information easier for users by having better organization in place from the outset. In this chapter, we build on this work and attempt to completely remove information keeping decisions by employing what Jones calls a "keep everything" strategy. We explore how we could build personal digital stores that save every bit of information we have touched or record every event we have experienced through our entire lifetime. We believe that this strategy has the potential to support users ranging from the most organized to the least organized (e.g., Alex, Connie, and Brooke). We examine the implications this has on how we organize and retrieve this information.